Clinical update on scorpion envenoming - Palmira Cupo (Revista da Sociedade Brasileira de Medicina Tropical, 2015)
Abstract: Scorpion stings are currently the leading cause of venom-related injury to humans in Brazil and are a significant public health problem globally. Only scorpions of the Tityus genus are of medical importance in Brazil, and Tityus serrulatus is responsible for the most serious envenomations and deaths. The toxic effects of scorpion envenomation are due to a massive release of sympathetic and parasympathetic neurotransmitters; the severity is related to cardiac and hemodynamic changes, with cardiogenic shock and pulmonary edema contributing to the main causes of death. The pathophysiology of cardiac involvement has been discussed for decades and has been attributed to adrenergic discharge and a possible toxic effect of venom on the myocardium, while acute pulmonary edema may have a cardiogenic and/or non-cardiogenic origin. Currently, the clinical data point to catecholamine excess as the cause for reversible scorpion cardiomyopathy . These data include electrocardiographic changes, profiling of cardiac enzymes and troponin I, echocardiographic data with global or regional left ventricle dysfunction, and myocardial perfusion alterations compatible with spasm in the coronary microcirculation. Furthermore, recent data on cardiac magnetic resonance imaging findings, which are similar to those observed for stress-induced cardiomyopathy, have also been linked to catecholamine excess. The efficiency of antivenom serum treatment is controversial in the literature. Our experience in Brazil is that the management of patients with systemic manifestations of scorpion stings is based on three approaches, all of which are extremely important. These include symptomatic treatment, antivenom serum, and cardiorespiratory support.